Metabolic changes during ramadan fasting in normal people and diabetic patients - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Mohd Shah, Azarisman Shah; How, Soon Hin (Faculty of Medicine, International Islamic University Malaysia, 2003)
Fasting is obligatory on all Muslims every year during the 9th Islamic lunar month of Ramadan with exemption to sick, travelers and pregnant women. In spite of the fact that Islam provides exemption from fasting to people suffering from illnesses like diabetes, many patients still want to fast for personal convictions. Physicians often face a dilemma as to how to advise them. Several studies have been published on the effects of fasting; some of the results are controversial. The present study was undertaken to establish the effects of Ramadan fasting on various physiological parameters in normal people and in diabetic patients. This could be used as basis for advice to such patients. The study group consisted of 53 diabetic patients (31 male and 22 female) and 56 (21 male 35 female) healthy volunteers as controls. Inclusion criteria of diabetic patients were: to be non-insulin dependent, and be stable and under reasonable control on oral hypoglycemic drugs and or diet control alone. The subjects were evaluated 1-2 weeks before commencement of fasting (visit 1), at the 4th week of Ramadan fasting (visit2) and one month after the end of the Ramadan fast (visit3). Blood samples were collected on each occasion at least 8 hours after the last meal. Our results showed statistically significant weight reduction (P<.001) at the end of Ramadan fast in both groups, however it was not maintained in both groups when values were compared before Ramadan and one month after Ramadan. Fasting blood sugar and HBA1C showed significant reduction (P<.001) among diabetics but not in control group. The other parameters e.g. cholesterol, blood urea and creatinine did not show any significant changes before and during Ramadan. There was statistically significant increase in serum cholesterol and triglyceride and uric acid (P<.001) among healthy volunteers (control group) one month after Ramadan compared to before Ramadan; however no such changes were seen among diabetic group. There was no reported case of serious complication due to fasting in both groups. Conclusion: Ramadan fasting lead to significant body weight reduction and improvement of glycaemic control in diabetic patients with out other significant metabolic changes.